Pregnancy and burns: experience of a university hospital burn unit - José Renato Nahlous Ferreira Leite; Erika Lopes Fernandes; Guilherme Ferreira Takassi; Andrea Fernandes de Oliveira; Lydia Masako Ferreira (Revista Brasileira de Cirurgia Plástica)
Introduction: The incidence of burns involving pregnant women is not well established in the literature, but is estimated to be between 3% and 7%. The management of burns in pregnancy represents a great challenge with significant impact on outcomes and maternal-fetal prognosis. Case Report: In the present study, we report two cases of pregnant burn victims who were treated in the burn unit in the Paulista School of Medicine, Federal University of São Paulo (EPM/UNIFESP). One patient was treated in the first trimester and the other in the third trimester. Conclusion: In both cases, the pregnant women received specialized treatment for burns in conjunction with clinical follow-up by the obstetrics team, with good maternal-fetal outcomes.